Effectiveness of Pelvic Floor Muscle Training and Yoga on the Quality of Life in Perimenopausal Women with Urinary Incontinence - Purba, Juliani (Nurse Media Journal of Nursing, 2021)
Background: Urinary incontinence is a symptom of genitourinary disease in perimenopausal women that can seriously affect both physical and mental health and quality of life (QOL). Pelvic floor muscle training (PFMT) and yoga are the exercises that have been applied to treat urinary incontinence. Research that compares the effect of PFMT and yoga on improving the quality of life of women with urinary incontinence is necessary. Purpose: This study aimed to compare the effectiveness of PFMT and yoga to improve the QOL in perimenopausal women with urinary incontinence.Methods: A quasi-experimental study with a nonequivalent control group design involving 48 perimenopausal women with all types of urinary incontinence was conducted. The participants were selected by consecutive sampling and equally divided into two groups. Each group was given the PFMT intervention and yoga exercise three times a week for eight weeks. The QOL was assessed using the incontinence impact questionnaire short form (IIQ-7). The data were analyzed by the Mann-Whitney U test, Wilcoxon signed rank test, and paired sample t-test.Results: The mean (standard deviation) score of total IIQ-7 in the PFMT group were lower (3.58 [2.57]) than that in the yoga group (5.17 [2.14]; p=0.061). There were differences in IIQ-7 score in the domains of physical activity (p<0.001), social relationships (p<0.001), and traveling (p<0.001) in the PFMT group. In contrast, in the yoga group, differences were found only in the emotional health domain (p=0.039). The IIQ-7 score was better in the PFMT group than in the yoga group.Conclusion: PFMT was as effective as yoga exercise to improve the QOL. PFMT and yoga should be taught to perimenopausal women with urinary incontinence.